DEVELOPMENT AND VALIDATION OF A RP- HPLC METHOD FOR DETERMINATION OF DIFLOXACIN RESIDUES IN DIFFERENT RABBIT TISSUES - Ahmed Said; Abd Elaleem Abd Elaleem; Sameh El-Nabtity; Sherief Abd Elhafeez (Slovenian Veterinary Research, 2021)
The occurrence of antibiotic residues in food of animal origin is attributed to incorrect drug administration or neglecting withdrawal times. These residues cause a lot of human health hazards, so it is important to control their presence. The aim of our study to evaluate a reversed phase- high performance liquid chromatography (RP- HPLC) method for determination of difloxacin residues in different rabbit tissues and serum post intramuscular injection of 5 mg/kg b.wt for 5 days and to investigate the withdrawal period of difloxacin in different rabbit tissues to be safe for human consumption. This method was validated to meet United States Pharmacopeia (USP) and the International Council for Harmonisation of Technical Requirements for Pharmaceuticals (ICH) guidelines. The separation was processed using buffer of triethylamine (pH:3.5) and acetonitrile (80 to 20, v.to v.) solvent on RP- C18 column at 35oC to obtain the ideal peak at 6.752 min. the separation was achieved at wavelength of 280 nm. Validation of analytical method has been done to keep up specifications such as specificity, linearity, precision, accuracy, sensitivity, repeatability, and robustness. The study showed high recovery, low detection limit, good precision. In addition, the rapid steps of the extraction process to be more economical and meet the requirements of green chemistry through minimum use of chemicals during sample extraction with little chemical waste production. Finally, residues of difloxacin were less than recommended maximum residue limits (MRL); 300, 600, and 800 ppb for muscle, kidneys, and liver; respectively on 1st day after treatment. Thus, Rabbit`s meat could be eaten safely on the 1st day after the end of treatment with 5 mg difloxacin/kg for 5 days.